TUN SRI LANANG DAN IKATAN KULTURAL ALAM MELAYU - Taufik Abdullah (LIPI Press, 2014)
The beginning of the 16th century can be seen as the time when the history of the two big powers in the Malay worldâ€“Majapahit and Malakaâ€“had ended and the period of â€œstable instabilityâ€ began. That was the time when the new emerging kingdoms were involved in the highly unstable relationship. Despite of the conflicts and uncertainties, the Malay literary tradition began during this period. Sejarah Melayu (Sulalat us Salihin) or Malay Annals is one of the most famous manuscripts in Malay literary tradition. It was written by Tun Sri Lanang, the Bendahara (â€œprime ministerâ€) of Johor (a kingdom on Malay Peninsula), who later became the district-head of Samalanga, Aceh- Darussalam. The manuscript does not only describe the history of the Malay kingdomsâ€“from the time of Palembang through the establishment of Malaka to the crisis of the Sultanate of Johorâ€“ but also discusses the ethics of power. This manuscript can be compared with Taj us Salatin, written in 1603. The basic foundation of power is justice. However, can the sense of justice be used to oppose the ruler, who has failed to perform the justice? Then, how are the dilemma between justice and rebellion be solved? Keywords: sirna ilang krta ning bhumi, Majapahit & Malaka, Sejarah Melayu, traditional historiography, political theory of Malay, justice and rebellion